2021
DOI: 10.1038/s41419-021-03774-w
|View full text |Cite
|
Sign up to set email alerts
|

The endoribonuclease N4BP1 prevents psoriasis by controlling both keratinocytes proliferation and neutrophil infiltration

Abstract: Psoriasis is a common chronic skin disease, characterized by abnormal interplay between hyperproliferative epidermal keratinocytes and self-reactive immune cells with not fully addressed molecular mechanism. N4BP1 (NEDD4-binding protein 1) is considered as an immune regulator for a long time but its physiological role is not determined yet. Here, we found that the expression of N4BP1 in skin was highest among all 54 tested tissues, and its expression was further upregulated in psoriatic skin. N4BP1-deficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…In this study, MCPIP1 and N4BP1 were confirmed to inhibit PRRSV replication, relying on their RNase activity. Both RNases belong to the Zc3h12a-like NYN domain subfamily of endoribonucleases and harbor a similar PIN-like domain with RNase activity ( 10 ). MCPIP1 is a spectrum antiviral RNase against various viruses, like HIV-1, by degrading viral mRNA ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, MCPIP1 and N4BP1 were confirmed to inhibit PRRSV replication, relying on their RNase activity. Both RNases belong to the Zc3h12a-like NYN domain subfamily of endoribonucleases and harbor a similar PIN-like domain with RNase activity ( 10 ). MCPIP1 is a spectrum antiviral RNase against various viruses, like HIV-1, by degrading viral mRNA ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte chemotactic protein-induced protein (MCPIP1), or Zc3h12a or Regnase-1, belongs to the Zc3h12a-like NYN domain subfamily of endoribonucleases. All members of the Zc3h12a-like RNase family have a similar PilT N terminus (PIN)-like domain with RNase activity, involved in antiviral immunity ( 10 ). MCPIP1 is a broad-spectrum antiviral protein, suppressing infection of HIV ( 11 ) and many other viruses.…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies have shown that N4BP1 was predominantly located in the nucleolus (Sharma et al , 2010; Gou et al , 2021), we evaluated the distribution of N4BP1 in the nucleus and cytoplasm. In the E14.5 brain, E18.5 dorsal telencephalon, cultured NPCs, and N1E‐115 cells, N4BP1 was distributed mainly in the cytoplasm, and few in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…NEDD4-binding protein 1 (N4BP1) is a nuclear RNase that degrades viral mRNA species in macrophages and primary T cells (23). N4BP1 also inhibits the production of proinflammatory cytokines and chemokines by inactivating AP-1 and NF-κB (22,24). The cleavage of N4BP1 by caspase-8 upregulates TLR4 ligand-induced cytokine production in mice, suggesting that ALN may degrade N4BP1 through the activation of caspase-8 (8).…”
Section: Introductionmentioning
confidence: 99%